Islamic Caliphate: Conflict of Beliefs in the State System in Indonesia - Ganes Harpendya; Siswo Hadi Sumantri; Bambang Wahyudi; Pujo Widodo; Herlina Juni Risma Saragih (CV. AFDIFAL MAJU BERKAH, 2023)
This article aims to describe and discuss the conflict of Islamic beliefs within the state system, with a focus on the concept of the Islamic caliphate (khilafah). Religious conflicts often arise due to differences in interpretation and contextualization of the application of religious laws. The conflicts that arise can lead to negative radicalism, extremism, and terrorism. The emergence of radical movements and terrorism is triggered by beliefs in religion that are believed to be the will of God. The Islamic caliphate, as one form of such movement, has diverse views among Islamic intellectuals, including right-wing extremists, left-wing extremists, and moderates. In this study, a qualitative descriptive method was employed with data collection techniques through literature review. The results and discussion of the article explain that the caliphate is a governing institution in Islam led by a caliph. There are differing views on the obligation to establish the caliphate. Some groups argue that establishing the caliphate is a duty for Muslims, while others reject this view. The views of Nahdlatul Ulama and Muhammadiyah in Indonesia are that Islam does not explicitly require the establishment of an Islamic state or caliphate. Both organizations argue that Muslims have the authority to design a governance system in accordance with the demands of time and place. This article provides an understanding of conflicts in religious beliefs, particularly related to the Islamic caliphate. With a better understanding of these differing views, it is hoped that society can avoid extremism, radicalism, and terrorism, which can threaten the nation and state's well-being.